Computers : faster, smaller, and smarter - Rooney, Anne. (Chicago : Heinemann Library, 2006)
Describes the history of the computer; aspects of modern life in which computers play a role; the future directions of computer technology, including nanotechnology and quantum computing; and cyber threats such as viruses and spyware.
The big picture -- Computers with and without people -- Wired world -- Robotics and artificial intelligence -- Imaging and modeling -- Cyber threats -- Faster and smaller -- Glossary.
Includes bibliographical references (p. 55) and index.
Library Media Connection.
School Library Journal.
7.9
5-8
Keywords: Computers -- Juvenile literature; Computers; Computers